Effectiveness of ethnomathematics-based visual thinking approach in increasing mathematics literacy and cultural motivation - Mefa Indriati; Turmudi Turmudi; Jarnawi Afgani Dahlan (International Journal of Trends in Mathematics Education Research, 2022)
This study is aimed to increase the students’ mathematics literacy and cultural motivation. The research design was a mix-method with an experiment with a nonequivalent control group design and ethnography. The research population was the junior high school students in the Siak City of Riau Province. The research sample was the students that were taken by using purposive sampling according to the research objective. The collection data techniques were interview, observation, and test. The interview with interview guidelines instrument to get information about the integration of culture with mathematics. The observation by a checklist to know the increasing motivation to learn and understand the Siak Culture. Test with an essay instrument to know the increasing the students' mathematics literacy after following the teaching process with the visual thinking method. The analysis data techniques were descriptive quantitative and t-test to know whether there was a difference between the control class and experiment class. The qualitative results show there were seven motifs of Tenun Siak that claimed in mathematics is Frieze F1 Pattern to F7 Pattern. The results show that there was a significant difference between the control class and the experiment class. The experiment class was better than the control class so it can be concluded that visual thinking can increase the students’ mathematics literacy. The motivation of students to learn and understand the Siak Culture from the first and sixth meetings also increases.